1990
DOI: 10.1289/ehp.908871
|View full text |Cite
|
Sign up to set email alerts
|

Rat liver endothelial and Kupffer cell-mediated mutagenicity of polycyclic aromatic hydrocarbons and aflatoxin B1.

Abstract: The ability of isolated rat liver endothelial and Kupffer cells to activate benzo(a)pyrene (BP), trans-7,8-dihydroxy-7,8-dihydrobenzo(a)pyrene (DDBP), trans-1,2-dihydroxy-1,2-dihydrochrysene (DDCH), and aflatoxin B, (AFB%) to mutagenic metabolites was assessed by means of a cell-mediated bacterial mutagenicity assay and compared with the ability of parenchymal cells to activate these compounds. Endothelial and Kupffer cells from untreated rats were able to activate AFB, and DDBP; DDBP was activated even in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…[27] Sinusoidal endothelial cells have been shown to possess cytochrome P450 activity [28] and to be targets of metabolic activation. [29] In addition, direct infusion of sources of superoxide and nitric oxide (i.e. the precursors of peroxynitrite) in an isolated perfused rat liver system resulted in morphological and structural alterations in liver sinusoids, consistent with the in vivo changes found in APAP toxicity.…”
Section: Resultsmentioning
confidence: 56%
“…[27] Sinusoidal endothelial cells have been shown to possess cytochrome P450 activity [28] and to be targets of metabolic activation. [29] In addition, direct infusion of sources of superoxide and nitric oxide (i.e. the precursors of peroxynitrite) in an isolated perfused rat liver system resulted in morphological and structural alterations in liver sinusoids, consistent with the in vivo changes found in APAP toxicity.…”
Section: Resultsmentioning
confidence: 56%
“…Previous data indicated that hepatic endothelial cells contain CYP enzymes (Oesch and Steinberg 1987; Steinberg et al 1990), and that activation of acetaminophen by CYP enzymes in endothelial cells may produce toxicity. Endothelial cells were isolated from two strains of mice.…”
Section: Alterations In Hepatic Blood Flow In Acetaminophen Toxicitymentioning
confidence: 99%
“…SECs have significant P450 activity and can metabolize drugs present in the portal circulation. [23][24][25] Metabolites exported across the sinusoidal pole of the hepatocyte enter the space of Disse, so that SECs may be exposed to higher concentrations of potentially toxic metabolites than are present in the hepatic vein or the systemic circulation. Because of this concentration gradient of toxic metabolites between the space of Disse and hepatic venous blood, SECs may be targeted by a mild toxic insult, whereas a more marked toxic insult is necessary to damage hepatic venular endothelial cells and endothelial cells in distant organs.…”
Section: Drug-induced Injury To Secsmentioning
confidence: 99%